(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Quality of Work Life is a very important aspect of every employee irrespective of the sector. It is no more an exception to the employees in Power sector. The employees of Power Sector have to work hard to solve the problems of the public. In this process they are unable to manage their work life balance. It is in this context the present study assumes significance. In this paper an attempt is made to present the various aspects of the quality of work life of employees of power sector with special reference to maintaining human relations.